Fast degradation of carbamazepine in water by electric discharge plasma - Gao, Shuzhan; Lu, Fu; Abid, Abid Ali; Yang, Xiyao; Wu, Zhengwei (Frontiers in Environmental Science, 2023)
The proliferation of pharmaceuticals in the aqueous environment has adversely impact on human health and ecosystem balance. Pharmaceutical contaminations are difficult to remove effectively by conventional treatment technologies. In order to degrade carbamazepine (CBZ) efficiently, a common antiepileptic drug, three plasma discharge modes were studied, including liquid-phase discharge, air gas-liquid jet and dielectric barrier discharge. It is noteworthy that the degradation efficiency and energy yield reached to highest levels (0.11g/kWh) when operating at 225 W input power under liquid phase discharge, compared with the other discharge modes. The parameters of concentration, electrode distance, volume, input power and frequency of the discharge were also evaluated and optimized. Plasma emission spectroscopy revealed the degradation process is mainly attributed to reactive oxygen species (ROS), while the role of reactive nitrogen species was not significant. The contributions of diverse ROS were assessed by radical quenching experiments, including p-benzoquinone, p-phthalic acid and tert-butanol. The possible degradation intermediates and pathways of CBZ were tested and analyzed by liquid chromatography-mass spectrometry (LC-MS). Comprehensively consideration of cleanliness, degradation efficiency and application difficulty, liquid-phase discharge treatment is a promising technology for water treatment.